Pengaruh Disiplin Kerja, Lingkungan Kerja, Dan Model Kepemimpinan Terhadap Loyalitas Kerja - Fitriyah Fitriyah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study is entitled to determine the effect of Work Discipline, Work environment and Leadership Models on Work Loyalty. In this research using quantitative methods. The sample in this study were Proseecing employees at PT Syngenta Seed Indonesia PIER, Pasuruan Regency with a sample size of 106 respondents who were taken using a purposive sampling saturated. The analytical method used is multiple linear regression analysis. To obtain the test results in this study, validity and reliability tests were carried out, classical assumption tests were normality and heroscedasticity tests, and then hypothesis testing was carried out. The results of this study show that the results of the Determination Test (R2) for the variable Work Motivation, Work Discipline, Work Environment and Leadership Model have an effect on Work Loyalty of 0.446 or the equivalent percentage value of 46.3%, while the remaining 55.4% is influenced by other variables . For the significant level, namely the the Work Environment variable has a nt significant effect Work Loyalty, while the Work Discipline variable has significant effect on Work Loyalty, and the Leadership Model variable has significant effect on Work Loyalty,